Entangled art historiographies in Ukraine
1 online resource.
Keywords: "This book explores ideologies, conflicts and ideas that underpinned art historical writing in Ukraine in the 20th century. Disciplinary beginnings testify both to its deep connection to Krakow, Saint Petersburg and especially Vienna with its school of art history and originality of theoretical thought. Art History started as another imperial project in Ukraine, but ultimately transformed into the means of assertion of national identity. The volume looks closely at the continuity and ruptures in scholarship caused by the establishment of Soviet power and challenges a number of existing stereotypes like total isolation under Communist rule and strict adherence to a Marxist-Leninist methodology. It showcases intellectual exchanges through published work, personal contacts, and ways to resist the politically enforced methodology. Despite keeping the focus on one country, it contributes to understanding the development of art history as an academic discipline in Europe more generally. It also uncovers unknown or little-researched personal and academic connections between art historians from Ukraine and their peers abroad. Starting with the 19th century quest for the method and proceeding by disentangling the complexities of the 20th century, the authors move on to the specifics of historiography after the formal collapse of the USSR. The volume transgresses purely academic boundaries and tackles the development of the discourse in periodicals, exhibition spaces and public discussions. Thus, the findings will be pertinent to all interested in politics, art history, museum studies, intellectual history, historiography, and Eastern European studies"--